Life cycle assessment of biodiesel production by using impregnated magnetic biochar derived from waste palm kernel shell - Arson Edberg, Erison; Hua Tan, Yie; Mubarak, N.M.; Jibrail, Kansedo; Mohammad, Khalid; Mohammad Omar, Abdullah; Mostafa, Ghasemi (Elsevier Science, Ltd., 2022)
Biodiesel is renewable, biodegradable, biocompatible (non-toxic) and environmentally friendly, which emits less pollution than traditional fossil-based diesel, making it the most promising and ideal option. However, biodiesel is facing many current issues, mostly related to the utilisation of homogeneous catalytic technology, and this circumstance obstructs its potential development and advancement. Therefore, new pathways for biodiesel production need to be explored, and the aforementioned issues need to be addressed. Recently, a study was conducted on the impregnated magnetic biochar derived from a waste palm kernel shell (PKS) catalyst that can replace conventional catalysts due to its reusability property. Nevertheless, the environmental impacts of impregnated magnetic biochar derived from waste PKS catalyst for biodiesel production are yet to be studied. This study focuses on the evaluation of the life cycle assessment (LCA) of palm-based cooking oil for biodiesel production catalysed by impregnated magnetic biochar derived from waste PKS. Simapro was used in this study to evaluate the impact assessment methodologies. Case 1 (6.64 × 102 Pt) has contributed less to environmental impacts than Case 2 (1.83 × 103 Pt). This indicates purchasing refined palm oil for biodiesel production may reduce environmental impacts by 64% compared to producing biodiesel from raw fruit bunches. In the midpoint assessment, the transesterification process was identified as the hotspot and marine aquatic ecotoxicity as the highest impact category with a value of 1.00 × 106 kg 1,4-DB eq for 1 tonne of biodiesel produced. The endpoint results showed that Case 1 revealed the greatest impact on the transesterification process, with cumulative damage of 461 Pt. Scenario without processing the raw palm fruit bunches to obtained palm oil was better than Case 2. Further research should be conducted on life cycle cost and sensitivity analysis to evaluate the economic feasibility and promote sustainable biodiesel production.